2020
DOI: 10.1002/cbdv.201900622
|View full text |Cite
|
Sign up to set email alerts
|

BF12, a Novel Benzofuran, Exhibits Antitumor Activity by Inhibiting Microtubules and the PI3K/Akt/mTOR Signaling Pathway in Human Cervical Cancer Cells

Abstract: BF12 [(2E)‐3‐[6‐Methoxy‐2‐(3,4,5‐trimethoxybenzoyl)‐1‐benzofuran‐5‐yl]prop‐2‐enoic acid], a novel derivative of combretastatin A‐4 (CA‐4), was previously found to inhibit tumor cell lines, with a particularly strong inhibitory effect on cervical cancer cells. In this study, we investigated the microtubule polymerization effects and apoptosis signaling mechanism of BF12. BF12 showed a potent efficiency against cervical cancer cells, SiHa and HeLa, with IC50 values of 1.10 and 1.06 μm, respectively. The cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The mechanistic studies showed that benzofuran derivative 12 induced G2/M phase arrest and apoptosis in SiHa and HeLa cells. 40 The in vitro antiproliferative activity of the benzofuran hybrids 13a-h was reported by Dharavath et al against two cell lines; C-6 (nerve cells) and MCF-7 (human breast adenocarcinoma cells) using the MTT method. The bioassay data of the in vitro antiproliferative activity disclosed that the benzofuran derivatives 13b and 13g demonstrated superior inhibition against MCF-7 cell line (with IC 50 1.875 and 1.287 mM, respectively), much better than the cisplatin drug (IC 50 2.184 mM).…”
Section: Anticancer Activity Of 2-benzoylbenzofuran Derivativesmentioning
confidence: 94%
See 1 more Smart Citation
“…The mechanistic studies showed that benzofuran derivative 12 induced G2/M phase arrest and apoptosis in SiHa and HeLa cells. 40 The in vitro antiproliferative activity of the benzofuran hybrids 13a-h was reported by Dharavath et al against two cell lines; C-6 (nerve cells) and MCF-7 (human breast adenocarcinoma cells) using the MTT method. The bioassay data of the in vitro antiproliferative activity disclosed that the benzofuran derivatives 13b and 13g demonstrated superior inhibition against MCF-7 cell line (with IC 50 1.875 and 1.287 mM, respectively), much better than the cisplatin drug (IC 50 2.184 mM).…”
Section: Anticancer Activity Of 2-benzoylbenzofuran Derivativesmentioning
confidence: 94%
“…The mechanistic studies showed that benzofuran derivative 12 induced G2/M phase arrest and apoptosis in SiHa and HeLa cells. 40 …”
Section: Anticancer Activity Of Benzofuran Derivativesmentioning
confidence: 99%
“…153,155 In vitro studies using cultured human cell lines show that TOR inhibition suppresses tubulin polymerization. 166 Depolymerization of microtubules with colchicine may increase cAMP formation (with a subsequent antifibrotic effect) 167 (Fig. 4).…”
Section: Protective Cardiovascular Effect Of Colchicinementioning
confidence: 99%
“…Some inhibitors of the PI3K/AKT/ TOR pathway (such as S9 and BF12) inhibit tubulin polymerization by binding to the colchicine domain of tubulin. 166,169 The activity of the PI3K/AKT pathway is upregulated in paclitaxel-resistant prostate cancer cells compared with paclitaxel-responsive prostate cancer cells, suggesting that activity of the PI3K/AKT pathway renders prostate cancer cells resistant to paclitaxel. 170 Interaction Between the Microtubule System and cAMP Signaling Microtubules contribute to regulate adenylyl cyclase activity, so that microtubule disassembly increases the synthesis of cAMP.…”
Section: Interaction Between the Microtubule System And Tor Signalingmentioning
confidence: 99%
“…However, the expression and mechanisms of miR-196a action in OSCCs are not well established. Previous studies have demonstrated that the PI3K/Akt pathway is activated in most types of cancer and suppresses the function of FOXO genes (18)(19)(20)(21)(22). The expression of FOXO1 is upregulated in human OSCCs and is significantly correlated with the advancement of clinical stages (23,24).…”
Section: Introductionmentioning
confidence: 99%